327 IS LOCAL ENDOSCOPIC RESECTION A VIABLE THERAPEUTIC OPTION FOR EARLY CLINICAL STAGE T1A AND T1B OESOPHAGEAL ADENOCARCINOMA? A PROPENSITY-MATCHED ANALYSIS. (14th September 2020) - Kamarajah, S; Phillips, A; Hanna, G; Low, D; Markar, S
Abstract: : The role of endoscopic resection (ER) in the management of subsets of clinical T1N0 oesophageal adenocarcinoma is controversial. The aim of this study was to evaluate the outcome of ER versus oesophagectomy in node negative cT1a and cT1b oesophageal adenocarcinoma. Methods: Data from the National Cancer Database (2010-2015), was used to identify patients with clinical T1aN0 (n = 2, 545) and T1bN0 (n = 1, 281) oesophageal adenocarcinoma that received either ER (cT1a, n = 1, 581; cT1b, n = 335) or oesophagectomy (cT1a, n = 964; cT1b, n = 946). Propensity score matching (PSM) and Cox multivariable analyses were used to account for treatment selection bias. Results: ER for cT1a and cT1b disease was performed more commonly over time. The rates of node-positive disease in patients with cT1a and cT1b oesophageal adenocarcinoma were 4% and 15%, respectively. In the matched cohort for cT1a cancers, ER had similar survival to oesophagectomy (HR: 0.85, 95% CI: 0.70-1.04, p = 0.1). The corresponding 5-year survival for ER and oesophagectomy were 70% and 74% (p = 0.1), respectively. For cT1b cancers, there was no statistically significant difference in overall survival between the treatment groups (HR: 0.87, 95% CI: 0.66-1.14, p = 0.3). The corresponding 5-year survival for ER and oesophagectomy were 53% vs. 61% (p = 0.3), respectively. Conclusion: This study demonstrates ER has comparable long-term outcomes for clinical T1aN0 and T1bN0 oesophageal adenocarcinoma. However, 15% of patients with cT1b oesophageal cancer were found to have positive nodal disease. Future research should seek to identify the subset of T1b cancers at high risk of nodal metastasis and thus would benefit from oesophagectomy with lymphadenectomy.